A study on reliability of Manets using trust management system - Bindu, G; Karthika, R.A.; Sridevi, S (International Journal of Engineering and Technology, 2018)
Mobile Adhoc Networks is a network where nodes keep moving geographically and doesnâ€™t have an infrastructure. This network is a challenging when interactions are critical to attain system goals like reliability, configurability, capability to increase the size of networks, rapid changes in topology of network, this effects the new nodes entering the network easily to attack. This makes difficult to maintain Trust management in the MANET. To overcome this, few algorithms are developed for Trust management. In this paper we discussed the different types of MANET, Applications, protocols and Trust management schemes. We tried to derive the trust management from different fields.Â